2021
DOI: 10.1101/2021.05.08.21256891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homebrew reagents for low cost RT-LAMP

Abstract: RT-LAMP (reverse transcription - Loop-mediated isothermal amplification) has gained popularity for the detection of SARS-CoV-2. The high specificity, sensitivity, simple protocols and potential to deliver results without the use of expensive equipment has made it an attractive alternative to RT-PCR. However, the high cost per reaction, the centralized manufacturing of required reagents and their distribution under cold chain shipping limits RT-LAMP applicability in low-income settings. The preparation of assay… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…While the RNA amplification step still requires commercial inputs, such reactions can also be made inhouse (Compton, 1991;Aufdembrink et al, 2020). Future work will focus on the in-house preparation of NASBA from locally purified, and IP-free RNAseH, T7 RNAP, pyrophosphatase, and reverse transcriptase enzymes (Aufdembrink et al, 2020;Reclone, 2020;Matute et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While the RNA amplification step still requires commercial inputs, such reactions can also be made inhouse (Compton, 1991;Aufdembrink et al, 2020). Future work will focus on the in-house preparation of NASBA from locally purified, and IP-free RNAseH, T7 RNAP, pyrophosphatase, and reverse transcriptase enzymes (Aufdembrink et al, 2020;Reclone, 2020;Matute et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Compton, 1991;Lauren M. Aufdembrink et al, 2020). Future work will focus on the in-house preparation of NASBA from locally purified, and IP-free RNAseH, T7 RNAP, pyrophosphatase, and reverse transcriptase enzymes (Lauren M. Aufdembrink et al, 2020;Reclone, 2020;Matute et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier work, we have reported the local production of a self-indicating mCherry fused BST LF with a silica binding tag for immobilization, that was produced locally in Ghana for a loop-mediated isothermal amplification (LAMP) for malaria diagnosis of clinical samples (Seevaratnam et al, 2022). The COVID-19 pandemic has also shown that the enzymes for RT-LAMP can be successfully produced in-house locally without the need for import of these vital reagents (Matute et al, 2021) and Mote et al have produced a PCR master mix with reagents produced in-house (Mote et al, 2021).…”
Section: Introductionmentioning
confidence: 99%